Odpowiedzi

2010-04-06T15:53:50+02:00
X/3+1=5/6+x/2 /*6
2x+6=5+3x
2x-3x=5-6
-x=-1/:(-1)
x=1

2x-3/4=1/2+x /*4
8x-3=2+4x
8x-4x=2+3
4x=5/:4
x=1¼

x+2/9+x-1/3=1/*9
9x+2+3(x-1)=9
9x+2+3x-3=9
12x=9+3-2
12x=10/:12
x= 5/6

2x+3/5=2-x/3+x/*15
3(2x+3)=5(2-x)+15x
6x+9=10-5x+15x
6x+5x-15x=10-9
-4x=1/(-4)
x= -1/4

3x-5/2-5x-1/10=0/*10
5(3x-5)-5x-1=0
15x-25-5x-1=0
10x=25/:10
x=5/2
x=2,5

x/2=2/5(4-x)-4
x/2=8/5-2/5x-4/*10
5x=16-4x-40
5x+4x=16-40
9x=-24/:9
x= 24/9

2x-1/5-x-2/2=0,7x/*10
4x-2-5x-10=7x
4x-5x-7x=2+10
-8x=12/:(-8)
x= - 1,5

2x-3x+5/4=-1/4x-1/*4
8x-3x+5=-1x-4
6x=-9/:6
x= 1,5